Liquidity, Leverage, and Profitability Effects on Firm Value in Pharmaceutical Healthcare Sector (2021–2024) - Revita Diaz Andini; Mar’atus Solikah; Faisol (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study analyzes the effect of liquidity, leverage, and profitability on firm value in pharmaceutical and healthcare sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024, motivated by declining firm value and inconsistent prior findings. Methodology: A quantitative causal design is used with secondary data from annual reports of 13 companies, resulting in 52 observations. The sample is selected using purposive sampling. Data are analyzed using panel data regression with the Random Effect Model (REM) in STATA 14. Results: Liquidity has no significant effect on firm value (p=0.415), leverage has a significant negative effect (p=0.028), and profitability is not significant (p=0.150). However, all variables jointly affect firm value. Conclusions: Leverage is the only significant determinant of firm value, while liquidity and profitability are not significant individually. Firms should manage capital structure more effectively to enhance investor confidence and firm value. Contribution: This study contributes empirically by providing evidence from the underexplored pharmaceutical and healthcare sector in Indonesia and clarifying inconsistent findings on liquidity, leverage, and profitability effects on firm value. It also enriches capital structure literature using panel data analysis. Limitations: This study is limited to 13 firms over a four-year period (2021–2024), which restricts generalizability. It only uses three financial variables and excludes macroeconomic and non-financial factors that may also influence firm value.